21-Gene Recurrence Score Assay and Outcomes of Adjuvant Radiotherapy in Elderly Women With Early-Stage Breast Cancer After Breast-Conserving Surgery - Wu, San-Gang; Zhang, Wen-Wen; Wang, Jun; Dong, Yong; Sun, Jia-Yuan; Chen, Yong-Xiong; He, Zhen-Yu (Frontiers in Oncology, 2019)
Introduction: To assess the role of the 21-gene recurrence score (RS) assay on decision-making of postoperative radiotherapy (RT) following breast-conserving surgery (BCS) in elderly women with early-stage breast cancer. Methods: The 21-gene RS for elderly (≥65 years) women with stage T1–2N0M0 estrogen receptor-positive breast cancer who underwent BCS from 2004 to 2015 was obtained from the Surveillance, Epidemiology, and End Results program. We estimated the association of 21-gene RS and adjuvant RT related to breast cancer-specific survival (BCSS) using propensity score matching (PSM). Results: We identified 18,456 patients, of which 15,326 (83.0%) received postoperative RT. Of identified patients, 58.9%, 34.0%, and 7.1% of patients had a low-, intermediate-, and high-risk RS, respectively. Receipt of postoperative RT was not related to the year of diagnosis according to the 21-gene RS groups. Multivariate analysis suggested that receipt of postoperative RT was an independent predictor of better BCSS before (hazard ratio [HR] 0.587, 95% confidence interval [CI] 0.426–0.809, P = 0.001) and after (HR 0.613, 95%CI 0.390–0.963, P = 0.034) PSM. However, subgroups analyses indicated that receipt of postoperative RT was related to better BCSS in women with intermediate-risk RS before (HR 0.467, 95%CI 0.283–0.772, P = 0.003) and after (HR 0.389, 95%CI 0.179–0.846, P = 0.017) PSM, but not in women with low- and high-risk RS groups before and after PSM. Conclusions: Although causation cannot be implied, adjuvant RT in elderly women was associated with a greater effect size in patients with an intermediate-risk RS.